Client Satisfaction in Health Service Management in Hospitals of Province One Eastern Nepal - Niraula, Tika Prasad; Poudel, Santosh Raj (Journal of Advanced Academic Research, 2019)
In health care organization, the satisfaction of client is the major factor which is directly linked with the effective use and the utilization of health care service. Effective and efficient management is a means to achieve predetermined goals. Organization cannot be successful unless it satisfies the clients. This descriptive cross-sectional study includes 680 patients which were selected from 4 public and 6 private hospitals randomly chosen from province 1. A direct interview method was used to gather and collect the data from clients' and hospital authorities for the quantitative method. The client satisfaction level was tabulated on the basis of 5 points liker scale. The reliability and the validity of the satisfaction scale for quantitative research we rechecked and examined. Association of categorical variables was assessed by Chi-square test. 92% of clients reported the higher satisfaction in the different aspects of nursing services .Around 31% of patients were completely not satisfied on "information regarding precaution of radio hazard", 26.8% on "waiting time to get the report" and 28.4% on "time consumed for report". About 28% of the participants reported not to be satisfied in the hospitals of Province 1for the availability of specialist in the emergency. The present study finding shows that 41.8 % of clients had reported any type of grievance towards health care service of hospital in Province 1.The study suggested that government should have first priority to allot sufficient specialized doctor services at least in district hospital and there should be 24 hours emergency duty of doctors. Laboratory and radio-diagnosis service in the hospital should be always be in good condition and reporting of the investigation should always be accurate as well as timely to make patients' satisfied in the hospital services. The gap of satisfaction level between private and public hospital may be fulfilled by the national health insurance system and the government should prioritize and implement the health insurance program with minimum premium.